Remote Working Intention of Gen Z in Vietnam - Ha, Nguyen Thi Viet; Thi Hien, Nguyen (International Journal of Scientific Research and Management (IJSRM), 2024)
Remote working is a way of working that creates flexibility for both employees and organizations when supported by the development of technology, which has been specially chosen by many agencies, organizations, and businesses in the wake of the Covid-19 pandemic. This research aims to identify the factors that influence Gen Z's intention to choose remote working at Hanoi (the capital of Vietnam). The theory research model was suggested based on the theory of TPB, TRA, TAM. The linear structure modeling (SEM) method was used to analyze the data of a sample with 400 observations collected by questionair survey in March and April 2021. The results show that two factors: "perceived behavioral control", and "social norms" have a positive and statistically significant impact on Gen Z's intention to work remotely in Vietnam. While the " attitude towards remote working" factor was impactful but not statistically significant